2007
DOI: 10.1111/j.1349-7006.2007.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Vector‐based Ape1 small interfering RNA enhances the sensitivity of human osteosarcoma cells to endostatin in vivo

Abstract: Osteosarcoma is a highly vascular and extremely destructive malignancy, and the survival of patients with osteosarcoma has not improved significantly in recent years. Antiangiogenic therapy currently holds great potential in conjunction with conventional treatment modalities for osteosarcoma. However, there are examples of gradual loss of response, and perhaps acquired resistance to antiangiogenic drugs. The acquired resistance of antiangiogenesis may be associated with a lot of hypoxia-response genes. The hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Wang et al 20 have observed an inhibition of human osteosarcoma xenografts in which the apurinic/apyrimidinic endonuclease gene has been downregulated by RNAi. For this, they have injected short hairpin RNA expression vectors into tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 20 have observed an inhibition of human osteosarcoma xenografts in which the apurinic/apyrimidinic endonuclease gene has been downregulated by RNAi. For this, they have injected short hairpin RNA expression vectors into tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies have predominantly decreased the expression of genes associated with cell cycle. [18][19][20][21] In osteosarcomas, one way to evaluate the therapeutic potential of small interfering RNA (siRNA) would be to target expression of RANKL in comparison with its blockage by antibody. However, the main challenge for the successful use of siRNA in vivo is to achieve an efficient delivery of these molecules to the target tissue without off-target effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that elevated APE/Ref-1 is associated with chemo-and radioresistance in a number of cellular systems (11,77,102). Knockdown of APE/Ref-1 efficiently induced apoptosis or sensitization or both to chemical treatments in many cancer cells (57,115,116,120).…”
Section: Increase Of Ape/ref-1 As An Adaptive Response To Oxidative Smentioning
confidence: 99%
“…Many of these genes are known to contribute to regulation of angiogenesis. We found that combined treatment with APE1 knockdown by RNA interference and recombinant human endostatin promoted apoptosis and had potent antiangiogenic effects in osteosarcoma through APE1-mediated regulation of VEGF expression 95. Our present data indicate that APE1 expression remained unchanged when A549 cells were treated with AT-101 or CDDP alone, or a combination of AT-101 and CDDP as compared with the control.…”
Section: Discussionmentioning
confidence: 49%